The combination of volumetric arc radiation therapy and boost high-dose rate interstitial brachytherapy for T3N2c tongue cancer: a technical report. (13th October 2022) - Murakami, Naoya; Sakuramachi, Madoka; Kashihara, Tairo; Chiba, Takahito; Nakamura, Satoshi; Ono, Keisuke; Ueno, Takao; Yoshimoto, Seiichi; Yoshida, Ken; Masui, Koji; Akiyama, Hironori; Igaki, Hiroshi
Abstract: Currently, tongue cancers are primarily managed by surgery, and interstitial brachytherapy is only recommended for a selected group of early state T1-2N0 patients who refuse surgery or are medically inoperable. In this report, a case with T3N2cM0 tongue cancer who has been effectively treated by the combination of concurrent chemoradiotherapy involving volumetric arc therapy and boost high-dose rate interstitial brachytherapy is presented. Of course, surgery remains the main treatment strategy for tongue cancer patients; however, the authors believe that if volumetric arc therapy is carefully planned to reduce the mandible dose as much as possible and high-dose rate interstitial brachytherapy with a mouthpiece that protects the mandible is combined, it is possible to treat T3N2 disease, and this can be considered for patients who want to preserve organ function. Abstract : This technical report discusses the use of high-dose rate interstitial brachytherapy boost combined with modern intensity-modulated radiation therapy and a dental mouthpiece for a locally advanced tongue cancer patient.